External control in public finance management - Tiossi, Fabiano Martin; Alves Cezane, Fernanda; Cardoso Medeiros de Castro, Patricia (Brazilian Journal of Production Engineering, 2020)
This study addresses the importance of external control in public finance management. In Brazil, the ownership of external control is constitutionally assigned to the legislature with the assistance of the Audit Courts. In this sense, the general objective of this article was to present how the process of oversight of external control bodies in public administration is developed and their role as a regulator of public spending. To comply with this proposal, a bibliographic and documentary research was conducted in processes exposed on the website of the Court of Auditors of the State of São Paulo, which were analyzed and confronted with current legislation. In addition, the role of external control according to the Federal Constitution of 1988 was described, besides the evolution of the Brazilian Public Administration, since it was from the practices directed to the Managerial Public Administration that the control process became more rigorous, due to the effective performance of external control agencies
Keywords: External control; Public finances; Court of auditors